Src-family protein tyrosine kinase phosphorylates WNK4 and modulates its inhibitory effect on KCNJ1 (ROMK) - Lin, Dao-Hong (Proc Natl Acad Sci U S A, 2015)
With-no-lysine kinase 4 (WNK4) inhibits the activity of the potassium channel KCNJ1 (ROMK) in the distal nephron, thereby contributing to the maintenance of potassium homeostasis. This effect is inhibited via phosphorylation at Ser1196 by serum/glucocorticoid-induced kinase 1 (SGK1), and this inhibition is attenuated by the Src-family protein tyrosine kinase (SFK). Using Western blot and mass spectrometry, we now identify three sites in WNK4 that are phosphorylated by c-Src: Tyr(1092), Tyr(1094), and Tyr(1143), and show that both c-Src and protein tyrosine phosphatase type 1D (PTP-1D) coimmunoprecipitate with WNK4. Mutation of Tyr(1092) or Tyr(1143) to phenylalanine decreased the association of c-Src or PTP-1D with WNK4, respectively. Moreover, the Tyr1092Phe mutation markedly reduced ROMK inhibition by WNK4; this inhibition was completely absent in the double mutant WNK4(Y1092/1094F). Similarly, c-Src prevented SGK1-induced phosphorylation of WNK4 at Ser(1196), an effect that was abrogated in the double mutant. WNK4(Y1143F) inhibited ROMK activity as potently as wild-type (WT) WNK4, but unlike WT, the inhibitory effect of WNK4(Y1143F) could not be reversed by SGK1. The failure to reverse WNK4(Y1143F)-induced inhibition of ROMK by SGK1 was possibly due to enhancing endogenous SFK effect on WNK4 by decreasing the WNK4–PTP-1D association because inhibition of SFK enabled SGK1 to reverse WNK4(Y1143F)-induced inhibition of ROMK. We conclude that WNK4 is a substrate of SFKs and that the association of c-Src and PTP-1D with WNK4 at Tyr(1092) and Tyr(1143) plays an important role in modulating the inhibitory effect of WNK4 on ROMK.